Diversity of Shrub Plants in Kapas Biru Waterfall Lumajang District of East Java - Barid Firdausy; Pujiastuti .; Siti Murdiyah (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2018)
The high diversity of plant species makes the Kapas Biru Waterfall a suitable area of tourism, research and other related activities. The plant species in this area are mostly seed plants and shrub. The shrub is a tree-like plant but with shorter and smaller main stem. The woody stems alsobranching near the surface of the soil. The aim of this research was to find out the species of shrub plants in the area of Kapas Biru Waterfall. This descriptive explorative research was conducted to systematically, factually and accurately describe and interpret the data of shrub seed plants in the area of Kapas Biru Waterfall. The study was conducted from April to May 2017. The research design included the selection of research sites, sampling and drawing, and plant identification stages.Samples were collected using total explore sampling method. Research result showed that there are 562 shrub plants in Kapas Biru Waterfall. They consist of 19 species incorporated in 11 families. Those family are Asparagaceae, Rutaceae, Asteraceae, Euphorbiaceae, Oleaceae, Arecaceae, Verbenaceae, Rubiaceae, Melastomataceae, Solanaceae, and Araliaceae. Keywords: Identifying, Kapas Biru, Shrub plants